Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Pembelajaran melalui Penggunaan Microsoft Teams Siswa Kelas XI SMA Yayasan Pupuk Kaltim Bontang Tahun Pembelajaran 2021/2022 - Arbiyanti, Arsya Amarlaily (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers in improving the quality of learning through the use of Microsoft Teams for eleventh-grade students at SMA Yayasan Pupuk Kaltim Bontang during the 2021/2022 academic year. Additionally, it explores whether Islamic Religious Education teachers can effectively enhance students’ learning quality in this context. The research aims to analyze the role of PAI teachers in utilizing Microsoft Teams as a learning medium. This study employs a qualitative research approach and was conducted at SMA Yayasan Pupuk Kaltim Bontang, located on Dahlia Street, PC-IV Housing Complex of PT. Pupuk Kaltim, Belimbing Subdistrict, West Bontang District, Bontang City, East Kalimantan Province. The research focuses on investigating the role of Islamic Religious Education teachers in enhancing learning quality through Microsoft Teams for eleventh-grade students. The data collection methods used in this study include observation, interviews, and documentation. The findings reveal that teachers face specific challenges in improving the quality of online learning for eleventh-grade students through Microsoft Teams. In response to these challenges, teachers adopt creative and innovative teaching strategies tailored to the students' conditions to enhance engagement and learning outcomes.